Transitioning with an Ostomy: The Experience of Patients with Cancer Following Hospital Discharge - Padilla, Liza L. (Université d'Ottawa / University of Ottawa, 2013)
The study aim was to describe the lived experience of patients with an ostomy due to cancer following hospital discharge, using a Heideggerian phenomenological lens. Colaizzi’s (1978) process guided a thematic analysis of nine unstructured interviews. The overall essence of patients’ transition experience was Adjusting to a New Way of Living. Four major themes emerged, Some Things are Different, Always on my Mind, Moving Towards Independence, and I’m Not Alone. Results suggest that the transition involves: adjusting to the ostomy and cancer; financial implications; changes in self, physical being, lifestyle, and social aspects of life; and psychological acceptance and preparation for the unexpected. Home care nurses and patients’ support network facilitated meeting their comprehensive care needs; while cancer treatments, the role of the significant other in the loss of privacy, funding inconsistencies, and temporary ostomy status were barriers. Patients need a comprehensive care approach to better facilitate the transition process.
Keywords: ostomy; cancer; transitions; hospital discharge; community; nursing; home care; Canada; Ontario